In-Orbit Attitude Determination of the UVSQ-SAT CubeSat Using TRIAD and MEKF Methods - Adrien Finance (MDPI AG, 2021)
Ultraviolet and infrared sensors at high quantum efficiency on-board a small satellite (UVSQ-SAT) is a CubeSat dedicated to the observation of the Earth and the Sun. This satellite has been in orbit since January 2021. It measures the Earth’s outgoing shortwave and longwave radiations. The satellite does not have an active pointing system. To improve the accuracy of the Earth’s radiative measurements and to resolve spatio-temporal fluctuations as much as possible, it is necessary to have a good knowledge of the attitude of the UVSQ-SAT CubeSat. The attitude determination of small satellites remains a challenge, and UVSQ-SAT represents a real and unique example to date for testing and validating different methods to improve the in-orbit attitude determination of a CubeSat. This paper presents the flight results of the UVSQ-SAT’s attitude determination. The Tri-Axial Attitude Determination (TRIAD) method was used, which represents one of the simplest solutions to the spacecraft attitude determination problem. Another method based on the Multiplicative Extended Kalman Filter (MEKF) was used to improve the results obtained with the TRIAD method. In sunlight, the CubeSat attitude is determined at an accuracy better than 3<semantics>°</semantics> (at one <semantics>σ</semantics>) for both methods. During eclipses, the accuracy of the TRIAD method is 14<semantics>°</semantics>, while it reaches 10<semantics>°</semantics> (at one <semantics>σ</semantics>) for the recursive MEKF method. Many future satellites could benefit from these studies in order to validate methods and configurations before launch.